WHAT IS NEW IN THE EU COHESION POLICY? - Natalia B. Kondratieva (Institute of Europe Russian Academy of Sciences, 2021)
Based on the review of regulations and press releases of EU institutions, the content of changes in the cohesion policy in 2021–2027 was revealed in comparison with the period 20142020. The conclusion is made about the preservation of a significant role of the cohesion policy in the EU’s activities and high volume of its allocations from the EU Budget. The author sees an element of novelty in the synthesis of well-known methods and principles of supranational regulation of the socio-economic development of the EU territories –the budget method, the principle of financial conditionality and the open method of coordination. Particular attention is paid to the decision to reorient a third of the allocations of European regional policy funds for programs of transition to a circular and climate-neutral economy in 2021–2027. The explanation of such strong link between the goals of regional policy and the ecological and climatic goals of the EU is proposed. Namely, the success of the «Europe 2020» Strategy only in terms of climate benchmarks, according to the author, gives to the official Brussels a reason to see the potential to increase the effectiveness of regional policy.